2018
DOI: 10.1210/jc.2018-01010
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety During and After Use of Phentermine and Topiramate

Abstract: ContextIncreases in heart rate were seen during the clinical program for fixed-dose combination phentermine (PHEN) and topiramate (TPM), an oral medication indicated for weight management; however, the effect on cardiovascular (CV) outcomes is uncertain.ObjectiveThe aim of the present study was to determine the extent to which the rates of major adverse CV events (MACE) in patients using PHEN and TPM (including fixed dose) differed from the MACE rates during unexposed periods.DesignRetrospective cohort study.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…The findings of this study reinforced previous results, which revealed that the drug can result in meaningful weight loss and favorable cardiovascular profile, including BP, lipid profiles, fasting glucose, fasting insulin, and waist circumference (WC). In a recent study, the occurrence of adverse cardiovascular events among the users of phentermine/topiramate ER was less frequent than the unexposed former users [ 40 ]. Meanwhile, a study that investigated the safety and efficacy of the drug used for the treatment of moderate-to-severe obstructive sleep apnea (OSA) in adults with obesity showed weight reduction as well as significant improvement in OSA as compared with the group treated with placebo.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study reinforced previous results, which revealed that the drug can result in meaningful weight loss and favorable cardiovascular profile, including BP, lipid profiles, fasting glucose, fasting insulin, and waist circumference (WC). In a recent study, the occurrence of adverse cardiovascular events among the users of phentermine/topiramate ER was less frequent than the unexposed former users [ 40 ]. Meanwhile, a study that investigated the safety and efficacy of the drug used for the treatment of moderate-to-severe obstructive sleep apnea (OSA) in adults with obesity showed weight reduction as well as significant improvement in OSA as compared with the group treated with placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Small, mostly transient, increases in heart rate are seen in some PHEN/TPM-treated subjects; however, there are no associated adverse clinical ramifications (28,29). Actually, in a very recent study, the major adverse cardiovascular events rates among current users of PHEN/ TPM combination were lower than those among unexposed former users (30). Furthermore, in a study conducted to evaluate the safety and efficacy of PHEN/TPM for the treatment of moderate-to-severe obstructive sleep apnea (OSA) in obese adults, treatment with PHEN/TPM led to significant weight reductions and concomitant improvements in OSA and related parameters, as compared with placebo.…”
Section: Phentermine/topiramatementioning
confidence: 99%
“…When accompanied by weight loss, many anti-obesity drugs reduce CVD risk factors (i.e., orlistat, liraglutide, naltrexone/bupropion, and phentermine/topiramate are not contraindicated in patients with cardiovascular disease) [ 3 ]. Little evidence supports phentermine & topiramate combination anti-obesity agent as increasing or decreasing CVD risk among patients with obesity [ 96 ]. Phentermine is contraindicated in patients with CVD [ 3 ] Among patients with obesity, CVD and type 2 diabetes mellitus without congestive cardiomyopathy, initial drug treatments to consider include metformin and GLP-1 RA (e.g., liraglutide, semaglutide), and SGLT-2 inhibitors (e.g., empagliflozin, canagliflozin) [ 3 ].…”
Section: Overweight and Obesitymentioning
confidence: 99%